Dying for France : experiencing and representing the soldier's death, 1500-2000 - Germani, Ian, 1957- (McGill-Queen's studies in the history of ideas, 2023)
"For centuries, the idea of dying honorably for France was extraordinarily potent, reaching its peak during the First World War when 1.4 million French soldiers died in uniform. By the end of the twentieth century, however, public opinion had come to view the soldier's death as an unacceptable tragedy, and also as an essentially private affair. Dying for France seeks to understand that profound shift by considering the soldier's death from the Renaissance to the present. It alights on important episodes in French military history-during the Renaissance and Old Regime, the French Revolution and Napoleonic Wars, the Franco-Prussia War and Paris Commune, the First World War, the Second World War, and the Algerian War-to consider the realities and the representations of military death. How did soldiers approach death or understand the dangers they faced, whether in battle or in military hospital, from wounds or from disease? How did it affect their view of war, or affect their conduct? In earlier centuries far more soldiers died of fevers and sickness than died in battle, while in Algeria, a major cause of death were accidents. How were the individual and collective deaths of soldiers seen by the people of France, and how were they represented in art, literature, and the popular press? This question was complicated by the fact that not all military deaths brought honour, and not all wars were seen as equally meritorious. Throughout Germani shows how appeals to chivalric values of "honour" and "patriotism" as justifications for military death have shown surprising continuity, despite significant changes to the content and contexts of those terms. In recent years, that language has struggled to maintain its hold, as death has retreated from everyday life and the soldier's death has become as unacceptable as any other. Yet as long as modern states require armed forces to defend their interests, they will need to find ways to digest the fact of the soldier's death. The author draws on many primary sources, especially the writings of soldiers, for evidence about how soldiers died, and how they dealt with the prospect of their own or their comrades' deaths. Representations of the soldier's death in newspapers, painting, and literary works are examined for what they reveal about social and cultural change."--